HIERARCHICAL BLOCK STRUCTURE OF ROCKS AND EMISSIONS OF SEISMIC WAVES IN UNDERGROUND EXPLOSIONS - Kitov I.O.; Stargan S.K.; Kuznetsov O.P. (My University, 1990)
Recent progress in the theory and methods of geomechanics has led to a clear understanding of previously unknown properties of the rock medium, particularly its block structure and structural hierarchy. The new theory holds that the rock medium consists of a hierarchical system of blocks separated by weak zones that are infilled with a low-strength material which readily undergoes plastic deformation. In the case of an underground explosion, the main signal from the seismic source is due to the movement of the rock on some spherical reference surface, beyond which the blast wave becomes elastic. The frequency of the spectral peak in the main signal is related to the diameter of the sphere and the velocity of elastic waves in the rock. Suppose that the main seismic signal generated in a shot is due to the movement, as a unit, of rock block of zero rank, and that the dimensions of this block are governed by the shot-generated deformation, rather than by the structure of the rock. Further, suppose that the high-frequency component of the signal is produced by the breakup of that zeroth rank block into blocks of first rank and their subsequent movement relative to each other. This entire process is irreversible. Then the frequencies of the spectral peaks of the main signal and of the high-frequency component will be in the same relation as the characteristic sizes of the blocks of the zeroth and the first ranks. To test this hypothesis, we evaluated several seismic traces recorded in the epicentral zones of underground blasts at frequencies between 1.0 and 25 Hz. The presence of distinct high-frequency vibrations superimposed on the low-frequency vibrations appears to confirm our hypothesis.